Parliamentarians' expenses recent reforms: A briefing on Australia, Canada, United Kingdom and Brazil - Leany Barreiro Lemos; Rosara Joseph (University of Oxford, Global Economic Governance Programme (GEG), 2010)
In 2009, the Australian, Brazilian and UK parliaments faced strong criticism - to say the least - over the issue of parliamentarians' expenses. The uncovering of widespread misuses of public resources by parliamentarians in each of these three countries was the subject of intense media and public attention, and prompted reform to the regulation and administration of the expenses regimes. This briefing is a descriptive account of the main features of these reforms. It addresses three key issues: (1) the nature of the response (short or long term); (2) the type of control system the reform has implemented (parliamentary self-regulation or regulation by external bodies); and (3) the nature of the content of the regulatory scheme itself (based on rules or principles). We also provide some background information on each country and some more detailed information on how the arrangements and systems for publicity, investigation and enforcement have been redesigned. The comparison of the three systems poses its challenges, as we have presidential and parliamentary systems with different historic backgrounds and traditions. Nevertheless, the similarities of the cases - both in how the misuses were uncovered and in how parliamentarians tried to placate public opinion by implementing immediate reforms - make the comparison worthwhile. More importantly, it identifies the experiences and lessons which may be useful for the ongoing reforms taking place in these countries. Canada was added for a different reason. Although its parliamentarians have not faced the same recent scandal and public scrutiny, we thought it might be useful to identify its approach to the regulation and administration
Keywords: 330; Parlament; Politiker; Lohn; Kosten; Australien; Kanada; Großbritannien; Brasilien